The Influence of Leadership Style on Employee Performance with Organizational Strategy as an Intervening Variable in BPJS Ketenagakerjaan Northern Sumatra Regional Office - Ginta Fernandes Ginting; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study was conducted to see the Influence of Leadership Style on Employee Performance with Organizational Strategy as an Intervening Variable. By using the type of quantitative research, primary data sources and data collection by conducting questionnaires and sharing them with responses, the population of this study is 80 employees and the sample used is also 80 respondents using the saturated sample technique as the sample technique, this research model uses analysis methods. The results of this study are as follows: Leadership Style has a positive and non-significant effect with a value of 0.053 and a significant value of 0.172 > 0.05 on. BPJS Ketenagakerjaan Sumbagut Regional Office. Leadership style had a positive and significant effect on Organizational Strategy with a value of 0.785 and a significant value of 0.000 < 0.05 on. BPJS Ketenagakerjaan Sumbagut Regional Office. Organizational Strategy has a positive and significant effect on Employee Performance with a value of 0.898 and a significant 0.000 < 0.05 at. BPJS Ketenagakerjaan Sumbagut Regional Office. Leadership Style has an indirect effect on Employee Performance positively and significantly through Organizational Strategy with a value of 0.705 and a significant 0.000 < 0.05 at. BPJS Ketenagakerjaan Sumbagut Regional Office.